The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.5603/gp.a2017.0099
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase inhibitors influence on the DIRAS3 and STAT3 expression and in vitro migration of ovarian and breast cancer cells

Abstract: Objectives: Downregulation of DIRAS3 (DIRAS family, GTP-binding Ras-like 3) is related to ovarian and breast cancer progression. A possible mechanism that silences this gene is the promoter region DNA methylation. The potential reversibility of this epigenetic mechanism makes it more attractive candidate for new mode of cancer treatment. DIRAS3 regulates cell cycle, tumor dormancy and inhibits cancer cell growth and motility, all of which may indirectly depend on interaction with STAT3 (Signal Transducer and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have demonstrated that DNA methylation and chromatin modulation may also be regulated by STAT-3 via epigenetic mechanisms (17,18). Moreover, STAT-3 has been recognized as a potent immune checkpoint regulator for…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that DNA methylation and chromatin modulation may also be regulated by STAT-3 via epigenetic mechanisms (17,18). Moreover, STAT-3 has been recognized as a potent immune checkpoint regulator for…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that MAP1LC3A was likeyly to play an indispensable role in the progression of BC. Nowak EM et al [22] revealed that DIRAS3 could regulate cell cycle and impair the growth and movement of cancer cells, all of which might be indirectly dependended on the interaction with STAT3. The down-regulation of DIRAS3 expression was related to the progression of BC, while the restoration of DIRAS3 expression could restain cell proliferation and invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, TAM-derived IL-6 and other cytokines activate STAT3 to promote tumor development by inducing proliferation and inhibiting apoptosis [ 26 ]. Many new drugs, such as DNA methyltransferase inhibitors, can promote tumor cell apoptosis, cell proliferation, angiogenesis, and distant metastasis by inhibiting the phosphorylation of STAT3 [ 27 30 ]. In addition, studies have shown that activated STAT3 (p-STAT3) can induce the expression of VEGF [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%